FACTORS AFFECTING THE PERFORMANCE OF HOSPITALS LISTED ON THE INDONESIA STOCK EXCHANGE IN THE PANDEMIC PERIOD - Adam Afiezan; Dena Viona Br Kembaren; Sri Wahyuni; Elisa Fransiska Girsang; Keulana Erwin (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Various policies implemented during the pandemic have resulted in lower business performance and increased spending. Research This was done to identify aspects that positively or negatively impact performance at home. During the pandemic, the working capital to assets, debt to capital, EBITDA margin, current ratio, and net income margin ratios were used to sicken that the deployed funds could serve the authority of some executives in the country. Expected. Tired of that need, especially in times of pandemic. The research conducted is a quantitative research. Merit sampling studies are conducted by non-probabilistic sampling, i.e. saturated sampling. The analyzes performed are classical test assumptions, including test normality, test multicollinearity, test autocorrelation, test heteroscedasticity, coefficient determination hypothesis, F-test, and T-test. The parameters WTCA, DER and NPM have a positive impact on the performance of houses listed in IDX 2018-2021, the parameter ebitda No has a negative impact on the performance and the parameter CR has a negative impact. Earnings Report The initial capital accumulation process is also well done to raise the profile of the company and the financials will be good